Comparison Between Whole-Body Vibration, Light-Emitting Diode, and Cycling Warm-up on High-Intensity Physical Performance During Sprint Bicycle Exercise. Issue 6 (June 2015) - Teles, Maria C.; Fonseca, Ivana A.T.; Martins, Jeanne B.; de Carvalho, Marielle M.; Xavier, Murilo; Costa, Sidney J.; de Avelar, Núbia C.P.; Ribeiro, Vanessa G.C.; Salvador, Fabiano S.; Augusto, Leonardo; Mendonça, Vanessa A.; Lacerda, Ana C.R.
Abstract : Abstract: Teles, MC, Fonseca, IAT, Martins, JB, de Carvalho, MM, Xavier, M, Costa, SJ, de Avelar, NCP, Ribeiro, VGC, Salvador, FS, Augusto, L, Mendonça, VA, and Lacerda, ACR. Comparison between whole-body vibration, light-emitting diode, and cycling warm-up on high-intensity physical performance during sprint bicycle exercise. J Strength Cond Res 29(6): 1542–1550, 2015—The purpose of this study was to compare the effects of light-emitting diode (LED) irradiation and whole-body vibration (WBV) delivered either in isolation or combination (LED + WBV), warm-up (WU), and a control (C) treatment on performance during a sprint bicycle exercise. Ten cyclists performed a 30-second sprint cycle test under these conditions. The LED light was applied at 4 points bilaterally. Whole-body vibration consisted of 5 minutes of squats associated with WBV. LED + WBV consisted of WBV followed by LED therapy. Warm-up consisted of 17 minutes of moderate-intensity bicycle exercise. Control consisted of 10 minutes at rest. Blood lactate (BL) and ammonia (BA) levels and skin temperature (ST) were determined. Peak power (842 ± 117 vs. 800 ± 106 vs. 809 ± 128 W [ p = 0.02 and p = 0.01]), relative power (12.1 ± 1.0 vs. 11.5 ± 0.9 vs. 11.6 ± 1.0 W·kg −1 [ p = 0.02 and p = 0.02]), and relative work (277 ± 23 vs. 263 ± 24 vs. 260 ± 23 J·kg −1 [ p = 0.02 and p = 0.003]) were higher in the WU group compared with the control and LED groups. In the LED + WBV group, peak (833 ± 115 vs. 800 ± 106 W [ p = 0.02]) and relative (11.9 ± 0.9 vs. 11.5 ± 0.9 W·kg −1 [ p = 0.02]) power were higher than those in the control group, and relative work (272 ± 22 vs. 260 ± 23 J·kg −1 [ p = 0.02]) were improved compared with the LED group. There were no differences for BL, BA, and ST. The findings of this study confirmed the effectiveness of a warm-up as a preparatory activity and demonstrated that LED + WBV and WBV were as effective as WU in improving cyclist performance during a sprint bicycle exercise.